Measuring the effect of happiness on GDP in Iraq for the period (1990-2019) - Dr. Ali Khalid Abdalaa; Asst. Prof .Dr. Zahid Q. Badan; Maan Abood Ali (Peerian Journals Publishing, 2022)
Happiness is a goal that everyone wants to achieve, as the researchers believe it is possible to calculate happiness in Iraqi society through three variables (human capital, economic wellbeing, and technological progress) Where the variables were described in a way that may be the first according to our knowledge, and after that the relationship between the variables and the gross domestic product (GDP) , was measured as an indicator of economic activity in Iraq ,And it turns out that the model is meaningful in the sense that the variables represent happiness in Iraq, as well as the existence of joint Cointegration between the variables in the long term
Keywords: Happiness; Human Capital; Economic Well-Being; technological progress